Assessing Students’ Learning: Revisiting Challenges of Secondary Mathematics Teachers in Bicol Region, Philippines - Sionicio, Joan Belen; Besmonte, Al Banico (Future Science / FSH-PH Publications, 2023)
The COVID-19 pandemic led to a sudden paradigm shift in education worldwide. To ensure that education would be undisrupted, many countries, including the Philippines, shifted from the usual face-to-face classes to distance learning modalities such as modular, online and blended. With these rapid changes, mathematics teachers were confronted with a lot of uncertainties. To investigate the challenges they encountered in assessing their students’ learning during the remote setting, this study used a descriptive research design. Data were gathered through online questionnaires in Google form and informal interviews among 268 secondary mathematics teachers from the different divisions in Bicol Region, Philippines. Thematic analysis was utilized in the analysis of qualitative data. Results show challenges in terms of the quality of outputs, materials and resources, students’ performance and feedback mechanism. On a positive note, they regarded the pandemic as an opportunity for professional advancement and pedagogical flexibility. The COVID-19 pandemic led to a sudden paradigm shift in education worldwide. To ensure that education would be undisrupted, many countries, including the Philippines, shifted from the usual face-to-face classes to distance learning modalities such as modular, online and blended. With these rapid changes, mathematics teachers were confronted with a lot of uncertainties. To investigate the challenges they encountered in assessing their students’ learning during the remote setting, this study used a descriptive research design. Data were gathered through online questionnaires in Google form and informal interviews among 268 secondary mathematics teachers from the different divisions in Bicol Region, Philippines. Thematic analysis was utilized in the analysis of qualitative data. Results show challenges in terms of the quality of outputs, materials and resources, students’ performance and feedback mechanism. On a positive note, they regarded the pandemic as an opportunity for professional advancement and pedagogical flexibility.